2019
DOI: 10.1093/neuonc/noz158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of cerebellar mutism syndrome in medulloblastoma

Abstract: Background Cerebellar mutism syndrome (CMS) is a common complication following resection of posterior fossa tumors, most commonly after surgery for medulloblastoma. Medulloblastoma subgroups have historically been treated as a single entity when assessing CMS risk; however, recent studies highlighting their clinical heterogeneity suggest the need for subgroup-specific analysis. Here, we examine a large international multicenter cohort of molecularly characterized medulloblastoma patients to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…According to our data, the development of CM after posterior fossa surgery in children appears to be a more complex phenomenon, requiring a combination of 1) surgery-unrelated factors (e.g., location of the tumor, medulloblastoma histology, brainstem infiltration) and 2) surgery-related factors (e.g., surgical manipulation near the dentate nuclei or the superior/middle cerebellar peduncles causing injury to the dento-rubro-thalamo-cortical pathways, inadequate use of self-retaining retractors and ultrasonic aspiration) ( 28 , 35 , 36 , 38 , 39 ). The risk factors identified in most papers ( 28 ) are mainly surgery unrelated: midline location (vermis and/or fourth ventricle), brainstem infiltration/compression, medulloblastoma histology with higher risk for 3–4 molecular subgroups ( 40 ), and tumor size ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, the development of CM after posterior fossa surgery in children appears to be a more complex phenomenon, requiring a combination of 1) surgery-unrelated factors (e.g., location of the tumor, medulloblastoma histology, brainstem infiltration) and 2) surgery-related factors (e.g., surgical manipulation near the dentate nuclei or the superior/middle cerebellar peduncles causing injury to the dento-rubro-thalamo-cortical pathways, inadequate use of self-retaining retractors and ultrasonic aspiration) ( 28 , 35 , 36 , 38 , 39 ). The risk factors identified in most papers ( 28 ) are mainly surgery unrelated: midline location (vermis and/or fourth ventricle), brainstem infiltration/compression, medulloblastoma histology with higher risk for 3–4 molecular subgroups ( 40 ), and tumor size ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found a higher or lower proportion of males in the pCMS group than in the non-pCMS group, but the difference was not significant. 8,[22][23][24] Linguistic studies have found that males lag behind females in early language development and are more vulnerable to language deficits than females. [25][26][27] We presume that the cerebellum may play an indispensable role in early language learning, especially for the Chinese language.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, four molecular subgroups of MB have been identified through transcriptional profile studies: sonic hedgehog [SHH], wingless [WNT], group 3, and group 4 (Ramaswamy and Taylor, 2017;Northcott et al, 2019). In this sense, it is interesting to note that several studies have recently identified the SHH subgroup as a significant factor in reducing the risk of post-operative CMS (Jabarkheel et al, 2020). The influence in the onset of post-operative CMS is probably the result of the cellular origin of a the subgroup rather than of the molecular characteristics: indeed, SHH medulloblastoma originates from the outer granular layer and therefore the tumor will typically develop within the cerebellar hemispheres; on the other hand, the origins from the lower rhombic lip, Nestin + cells, and unipolar brush cells, respectively of the WNT subgroups, 3 and 4 (Vladoiu et al, 2019), will give rise to tumors with an intimate relationship with the structures of the fourth ventricle, causing a greater risk of damage to the DRTT pathway during resection.…”
Section: Risk Factors and Risk Stratificationmentioning
confidence: 99%